Bicultural, personality, and pedagogical competences in the perspective of BIPA language assistants - Syihabuddin Syihabuddin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Bicultural, personality, and pedagogical competences in the perspective of BIPA language assistantsIn 2019, there were 63.022 learners of Indonesian as a foreign language in Victorian schools, Australia. They were facilitated by 263 Indonesian Language for Foreign Speakers (BIPA) local teachers. Due to a shortage of BIPA local teachers, the Department of Education and Training Victoria had recruited language assistants from Indonesia. This study is aimed to describe the required skillsets of BIPA language assistants to support their duties. The data were collected through interviews, an inventory, observations, and stories of eight Indonesian language assistants with one year of experience. The findings reveal that the language assistants need to develop bicultural, personality and pedagogical competences. These competences should become the reference for developing workshop materials for future BIPA language assistants.Keywords: BIPA teachers, bicultural competences, personality competences,  pedagogical competencesKompetensi bikultural, kepribadian, dan pedagogik dalam perspektif guru bantu BIPAPada tahun 2019 terdapat 63.022 siswa Victoria, Australia, yang mempelajari bahasa Indonesia sebagai bahasa asing. Mereka dibimbing oleh 263 guru BIPA. Karena jumlah guru tidak memadai, maka Department of Education and Training Victoria merekrut guru bantu (language assistant) dari Indonesia. Penelitian ini bertujuan untuk mendeskripsikan berbagai kompetensi yang perlu dimiliki guru bantu untuk menunjang pelaksanaan tugasnya. Data dikumpulkan dari wawancara, inventori, observasi, dan deskripsi pengalaman dari delapan guru bantu selama satu tahun mengajar. Hasil penelitian menunjukkan bahwa guru bantu perlu mengembangkan kompetensi bikultural, kompetensi kepribadian, dan kompetensi pedagogik. Ketiga kompetensi ini sebaiknya dijadikan bahan workshop pada pembekalan guru bantu di lembaga pengirim.Kata kunci: guru BIPA, kompetensi bikultural, kompetensi kepribadian, kompetensi pedagogik